Stratégies de réplication dynamique dans les grilles de données - BOUHARAOUA Farouk (My University, 2007)
Nowadays, the grid environment presents new challenges, such as the dynamic availability of various resources that are geographically distributed, the quick and the efficient access to data, reduction of time of latency and fault tolerance. These grids are concentrated on the reduction of the execution time of the applications that require a great number of processing cycles by the computer. In such environment, these advantages aren’t possible unless by the use of the replication. This later is considered as an important technique to reduce the cost of access to the data in grid. In this context, we present our contribution to Dynamic Replication Strategies, whose objective is to reduce the cost of access to replicated data. The placement decisions are based on cost model, which depend on many factors like the bandwidth, data size and the number of the read and write operations.
Keywords: Data grid, replication, data placement, cost model, CERN.